Green Banking Disclosure and Financial Performance: Role of Corporate Governance as Moderating Variable - Rahmamita, Deane; Kahar, Muhammad Ridwan (Pusat Studi Pembangunan dan Pemberdayaan, 2024)
This study intends to examine the positive impact of green banking disclosure on financial performance and the role of corporate governance in strengthening this relationship. The sample consists of BUKU IV banks listed on the Indonesia Stock Exchange from 2019–2024, using moderated regression analysis (MRA). The results show that green banking disclosure positively impact market financial performance (Tobin’s Q), with corporate governance strengthening the relationship. However, green banking disclosure does not influence operational performance (ROA and ROE), and corporate governance does not moderate this relationship. Overall, green banking disclosure, supported by good corporate governance, enhances market value and global competitiveness, especially for BUKU IV banks.